Hubungan umur, masa kerja dan kuliah online dengan produktifitas dosen pada masa pandemi covid-19 di Universitas “X” kota Semarang. - Supriyono Asfawi; MG Catur Yuantari; Yusthin M Manglapy; Yohanes Pratama; Rini Wulandari Hariono; Wening Wiworo Palupi (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
During the COVID-19 pandemic, the teaching and learning process must continue, work from home is one solution for its implementation. The obligation of lecturers to carry out the Tri Dharma of Higher Education must still be carried out as a benchmark for the success and productivity of lecturers. This study aims to see the level of productivity of lecturers during the covid-19 pandemic at the "X" university in Semarang city. The results show that lecturer productivity as measured by the Lecturer Workload (BKD) parameter is in the good category with the number of respondents for 29 lecturers (53%), the rest in the lesser category. But overall productivity is better during the pandemic.